Using QuickBooks® Online for Accounting 2021, 4th Edition - Glenn Owen (Cengage Learning, 2020)
Master the skills of QuickBooks® Online Accountant (QBOA) at your own pace with the unique self-directed learning approach found in Owen's USING QUICKBOOKS® ONLINE FOR ACCOUNTING, 4E. This edition focuses exclusively on QBOA, allowing you to refine your skills while reviewing your understanding of financial accounting, reporting and analysis tools. You learn how accounting information is both created and used to make key decisions. Easy-to-follow instructions, real examples and manageable assignments help you reinforce your accounting skills as you practice using the QBOA application and analyzing business events. You learn how to set up QBOA for a business and how to use it to record business events; generate financial statements and reports; and communicate critical information to business owners, investors and creditors. The skills you acquire translate into on-the-job success no matter what accounting applications you use in the future.